HLA-DRB1 and HLA-DQB1 genetic polymorphisms and susceptibility to coronary atherosclerosis in a Northeast Chinese Population: A case-control study - Miaomiao Niu; Jing Gao; Xiaodong Han; Ying Dong; Hui Wang; Yue Zhang; Dongming Zhao; Zijian Wang; Fang Qi; Feng Wang; Qiuye Meng; Jinjiao Geng; et al. (PLoS ONE, 2026)
Atherosclerosis is a chronic inflammatory disease with increasing prevalence in Northeast China, where HLA class II molecules play an important immunoregulatory role. However, the contribution of specific HLA-DRB1 and HLA-DQB1 alleles to AS susceptibility in this population remains incompletely characterized, necessitating novel biomarkers for early detection. In this case-control study of 209 participants, HLA-DRB1 and HLA-DQB1 allele and phenotypic haplotype distributions were compared using odds ratios with 95% confidence intervals and Bonferroni correction for multiple comparisons. A total of 28 HLA-DRB1 and 12 HLA-DQB1 alleles were analyzed. The lowest P value for HLA-DRB1 was observed for DRB1*07:01 ( P = 0.077, corrected P = 1.000; OR = 1.994, 95% CI: 0.955–4.164), and that for HLA-DQB1 was observed for DQB1*02:02 ( P = 0.150, corrected P = 1.000; OR = 1.739, 95% CI: 0.850–3.558). Neither reached statistical significance, though both trended upward in the AS-susceptible group (DRB1*07:01: 12.59% vs. 6.76%; DQB1*02:02: 12.22% vs. 7.43%). The DRB1*07:01-DQB1*02:02 phenotypic haplotype was more frequent in the AS-susceptible group than in the control group (22.22% vs. 10.81%), with an OR of 2.357 (95% CI: 1.019–5.452). Although the association did not survive Bonferroni correction (corrected P = 1.000), the effect size suggested the signal was unlikely to be a trivial statistical artifact. In conclusion, the DRB1*07:01-DQB1*02:02 phenotypic haplotype was identified as a candidate risk marker for AS in the Northeast Chinese population, warranting validation in larger cohorts.